Evaluation of Doppler Indices and Fetal Outcome In Normal and Pre-Eclampsia Patients (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Preeclampsia (PE) is one of the major risk factors in maternal mortality. The impairment in placental perfusion due to vascular abnormalities leads to clinical manifestationsand isevident by Doppler ultrasound. Doppler velocimetry is a rapid, non-invasive and efficient diagnostic test to detect fetal jeopardy. Objective of the study is to observe the fetal outcome in Preeclampsia cases by using Doppler ultrasound study after 30 weeks of gestation and comparing these with normal controls.Materials and methods: This case control study was conducted in the Department of Obstetrics and Gynecology, Khulna Medical College Hospital between 1st September 2019 and 28th  February 2020. Thirty-three  pregnant women after 30 weeks of gestational age who were clinically diagnosed as preeclampsia were selected as cases (Group I) and equal number (33) of age, parity and gestational age group matched apparently healthy normotensive pregnant women were selected as control (Group II) for the study. Then each patient was subjected to color Doppler study and ultrasound examination. All clinical and socio-demographic information were collected in a pre-designed separate case record form. Data were analyzed by using Statistical Package for Social Science (SPSS) version 22.0.Results: There was no remarkable difference in Doppler study findings of uterine artery between both groups Regarding umbilical artery, both mean RI (0.73±0.25 vs 0.62±0.11) and mean PI (1.18±0.35 vs 0.82±0.15) was significantly different in two groups with lesser perfusion in preeclampsia group. Regarding middle cerebral artery, mean RI(0.76±0.20 vs 0.86±0.32) and mean PI (1.32±0.29 vs 1.48±0.29) was significantly different in two groups with lesser perfusion in preeclampsia group. Regarding fetal outcome, fetal birth weight, (1.76±0.44 kg vs 2.67±0.63 kg), APGAR score at 1 min,(5.24±1.25 vs 5.85±0.83) and APGAR score at 5 min (8±1.50vs 8.82±0.58) was statistically different between both groups with more frequency of adverse outcome in preeclampsia group. There was no significant difference in NICU  admission and perinatal death.Conclusion: This study observed high incidence of low birth weight and low APGAR score with abnormal Doppler in preeclampsia group. So, Color Doppler study can be used as an adjunct in pre-eclampsia with adverse fetal outcome.JCMCTA 2023 ; 34 (2) : 101-106